IMPLEMENTASI PENDEKATAN DEEP LEARNING DALAM PEMBELAJARAN IPAS KELAS III DI SDN 17 MATARAM - Zadira, Alfiah; Muhammad Sobri; Ilham Handika (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe the implementation of the Deep Learning approach in Science and Social Studies (IPAS) learning for third-grade students at SDN 17 Mataram, covering lesson planning, learning implementation, learning evaluation, as well as the supporting and inhibiting factors affecting its implementation. This study employed a qualitative approach with a descriptive research design. The research participants consisted of the principal, the third-grade classroom teacher, and three third-grade students. Data were collected through observations, interviews, and documentation. The findings revealed that the implementation of the Deep Learning approach in IPAS learning at SDN 17 Mataram had been carried out effectively. During the planning stage, the teacher prepared teaching modules, formulated learning objectives, selected appropriate teaching methods and instructional media, and designed learning activities that integrated the principles of mindful learning, meaningful learning, and joyful learning. In the implementation stage, the teacher applied student-centered learning through observation, discussion, group work, presentations, problem-solving activities, and reflection, enabling students to actively participate in the learning process. Learning evaluation was conducted continuously through process and outcome assessments to monitor students' conceptual understanding. The implementation of the Deep Learning approach was supported by teachers' competencies, the principal's support, the availability of learning facilities, and students' enthusiasm. However, several challenges were identified, including differences in students' learning abilities, limited availability of certain instructional media, and the need for teachers to continuously enhance their creativity in designing contextual learning. activities. Overall, the implementation of the Deep Learning approach successfully created an active, meaningful, and enjoyable IPAS learning environment while fostering students' deeper conceptual understanding